Prevention of Water Inrushes in Deep Coal Mining over the Ordovician Aquifer: A Case Study in the Wutongzhuang Coal Mine of China. (15th September 2021) - Yin, Huichao; Xu, Bin; Yin, Shangxian; Tian, Wuzi; Yao, Hui; Meng, Haopeng
Abstract : Through field observation and theoretical study, we found that the Hanxing mining area has a typical ternary structure in coal mining under high water pressure of the aquifer. This ternary structure is the Ordovician limestone aquifer-aquiclude including thin limestones-coal seam. Although the aquiclude is considerably thick, there is still a great risk of water burst during mining under water pressure in the deep burial environment. Multidimensional characteristics of floor water inrush in deep mining are summarized in the paper, including water migration upwardly driven by the Ordovician confined water, the planar dispersion of the water inrush channel, the stepped increase of the water inrush intensity, the hysteretic effluent of the water inrush time and the exchange, and adsorption of the water quality. The water inrush mechanism is clarified that the permeability, dilatancy, fracturing, and ascending of the water from the Ordovician limestone aquifer form a planar and divergent flow through the transfer, storage, and transportation of thin limestone aquifers. The corresponding water inrush risk evaluation equation is also proposed. Based on the thickness of the aquiclude, the thickness of the failure zones, and the water inrush coefficient, the floor aquiclude is classified into five categories. While water inrush cannot be completely controlled by the traditional underground floor reinforcement with ultra-thick aquiclude or even zonal grouting, a comprehensive prevention and control concept of the four-dimensional floor water hazard in full time-space domain are proposed. A tridimensional prevention and control model of three-dimensional reticulated exploration, treatment, verification, and supplementation is presented. A full time domain technological quality control process of condition assessment, exploration, remediation, inspection, evaluation, monitoring, and reassurance is formed, and a water disaster prevention method with full time-space tridimensional network in deep coal mining is established. Case study in the Hanxing mining area demonstrates that the proposed methods are highly effective.